2020
DOI: 10.1002/zaac.201900351
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Gallium and Cobalt‐Gallium Tetraphosphido Complexes

Abstract: The synthesis and characterization of two heterobimetallic complexes [K([18]crown‐6){(η4‐C14H10)Fe(μ‐η4:η2‐P4)Ga(nacnac)}] (1) (C14H10 = anthracene) and [K(dme)2{(η4‐C14H10)Co(μ‐η4:η2‐P4)Ga(nacnac)}] (2) with strongly reduced P4 units is reported. Compounds 1 and 2 are prepared by reaction of the gallium(III) complex [(nacnac)Ga(η2‐P4)] (nacnac = CH[CMeN(2,6‐iPr2C6H3)]2) with bis(anthracene)ferrate(1–) and ‐cobaltate(1–) salts. The molecular structures of 1 and 2 were determined by X‐ray crystallography and fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Heterobimetallic complexes with highly reduced P 4 ligands, derived from iron and cobalt metalates, were reported in 2020 by Wolf, Weigand and co-workers . The metalates [M­(η 4 -C 14 H 10 ) 2 ] − [M = Fe ( 52 ); Co ( 14 )] reacted with the gallium tetraphosphido species [(nacnac)­Ga­(κ 2 -P 4 )] ( 1049 , nacnac = CH­[CMeN­(2,6- i Pr 2 C 6 H 3 )] 2 ), which contains an activated (butterfly) P 4 unit .…”
Section: Metalates In Small-molecule Activation and Catalysismentioning
confidence: 99%
See 3 more Smart Citations
“…Heterobimetallic complexes with highly reduced P 4 ligands, derived from iron and cobalt metalates, were reported in 2020 by Wolf, Weigand and co-workers . The metalates [M­(η 4 -C 14 H 10 ) 2 ] − [M = Fe ( 52 ); Co ( 14 )] reacted with the gallium tetraphosphido species [(nacnac)­Ga­(κ 2 -P 4 )] ( 1049 , nacnac = CH­[CMeN­(2,6- i Pr 2 C 6 H 3 )] 2 ), which contains an activated (butterfly) P 4 unit .…”
Section: Metalates In Small-molecule Activation and Catalysismentioning
confidence: 99%
“…Magnetic measurements (Evans method and SQUID) indicated that 1064 is a mixed-valent Co I −Co II species, while in 1065 the cyclo-P 3 3− unit bridges two Co(II) centers. 635 386,632 This procedure afforded the heterodinuclear cobalt−gallium compounds [K(dme) 2 {( Ar BIAN)Co(μ-η 4 :κ 2 -P 4 )Ga(nacnac)}] [ Ar BIAN = Dipp BIAN (1069), Mes BIAN (bis(mesitylimino)acenaphthenediimine) (1070)], featuring catena-P 4 ligands. Reactivity studies performed on 1070 showed that these complexes can be functionalized with alkylchlorophosphanes (R n PCl 3−n ) to afford polyphosphorus cyclo-P 5 R 2 compounds.…”
Section: General Remarks On White Phosphorusmentioning
confidence: 99%
See 2 more Smart Citations